The Woman’s Images in William Wordsworth’s Poem - Miftahul Khairi (Jambura Journal of English Teaching and Literature, 2020)
Literature and woman’s images have a strong relationship, particularly in poetry. Some poets use the women as the main object of their works. This study explored the woman’s images in some Wordsworth’s poems; She was a Phantom of Delight, The Solitary Reaper and To a Highland Girl. Those poems could be represented of his works because woman’s figure is so strong and observable in there. New Criticism is the approach which is used in analyzing those poems. Hence, the outcome of this study is the interpretation of woman’s illustration purely in the Wordsworth’s poems. Consequently, this research will utilize the descriptive qualitative research methodology. In data collecting, the research is collected based on the line(s) or stanza(s) which is/are contain the woman’s image figuratively and Imagery. 20 data are found as the result of this study. Therefore, the data is analyzed by using componential analysis to categorize figurative language or imagery. It is apportioned the data according to the theory of intrinsic element of poem. Furthermore, the exploration of the data finding is supported by the interpretation as one of the main points in this scrutiny. Therefore, the all data were substituted into 5 woman’s images categories. They are Mystery, Beauty, Independent, Great and Grace, and Loneliness which are mostly dominated by metaphor and visual imagery, where each of them from figurative language and imagery. This research is constructively developing the study of literature, particularly in poem matter. Moreover, further recommendation for collecting wider explanation is offered in the study.